A town called eco: What notions of sustainable development do the government's proposed eco-towns embody? - Sean Rose (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
The eco-towns agenda is intended to address social and environmental concerns through facilitating exemplar new sustainable settlements. Sustainable development, which traditionally combines environmental, economic and social aspects of sustainability, has recently been adopted as a cogent Government Policy. This research asks what notions of sustainable development have been embodied in the Government eco-towns agenda. Research consisted of nineteen semi-structured interviews with those involved in eco-towns design and delivery, and the wider sustainability movement. Archival research helped to position the agenda and trace its evolution. The results suggest that the Government has failed to account for the full complement of sustainable development notions in developing these eco-towns. There is a focus on environmental aspects, particularly the concept of zero-carbon, arguably at the expense of broader considerations. Eco-towns set a precedent for increased private sector involvement in the agenda, but employment provision within the settlements has not been thought through and they could thus become unsustainable economically. Social notions of sustainable development have been weakly integrated into the agenda and this threatens to undermine its overall success. It is argued that whilst an important move in the right direction, eco-towns are an imperfect idea and could benefit from refinement. In particular they could set more systematic environmental targets, such as for zero-carbon, and may be more successful communities if they challenged the very model through which new towns such as these are delivered.
Keywords: 330; Eco-towns; Sustainable Communities; New Settlements; Sustainable Development; Kommunalplanung; Nachhaltige Entwicklung; Umweltpolitik; Großbritannien